Evaluasi Penggunaan Obat Analgetik Pada Pasien Osteoartritis di Instalasi Rawat Jalan RSUD Dr. Moewardi Surakarta Tahun 2015 - Parandhita, Heldha Ayu, Hidayah Karuniawati, M.Sc., Apt (2016)
Osteoarthritis (OA) is a chronic rheumatic disease that is a major cause loss of physic function and disability. Osteoarthritis may affect several joints in the neck, hips, knees, five bones in the fingers and toes. Prevalention osteoarthritis in Indonesia reached 36.5 million people in 2007 where the majority patients are elderly. Osteoarthritis patients feel pain that will affect on reduced quality of life's patients. The purpose of this study are to describe and evaluate analgesic prescription in patients with osteoarthritis at Dr. Moewardi Surakarta Hospital in 2015 based on parameters proper indication, proper patient, proper drug and proper dosage. This study was a non experimental research. Data was obtained retrospectively from medical records of patients with osteoarthritis. Data was descriptively analyzed one hundred patients were included as sample by purposive sampling method. Inclusion criteria of this study was patient's with osteoarthritis who accept analgesics prescription in 2015 with complete medical record. Exclusion criteria of this study was pregnant patients. An overview of analgesic use in osteoarthritis patients starting from the highest are paracetamol (42%), sodium diclofenac (38%), meloxicam (10%), metampiron (3%), mefenamic acid (4%), ibuprofen (2%) and celecoxib (1%). The result of this study is 100% proper indications, 71% proper patient, 71% proper drug and the 55% proper dosage.